Eficacia del tramadol 100 mg vía parenteral intramuscular en el manejo de analgesia del trabajo de parto - Angeles Reyes, Robert Peter (2022)
With this study, it is expected to demonstrate the efficacy of parenteral tramadol to relieve the intensity of labor pain, in pregnant women at term with a fetus with a cephalic presentation who attend the Trujillo Regional Teaching Hospital for delivery care, verifying the action of the tramadol to relieve the pain of labor, in the expulsive period and delivery, and the adverse effects that they present in mother and child. Two study groups will be assigned, one with the use of intramuscular tramadol in a single dose and the other with placebo, in a randomized, double-blind manner. The ESVADOPA scale will be used to measure the intensity of pain, applied at the time of patient admission to the study, at one hour and then every 2 hours, during labor and delivery. Adverse effects on the mother and fetus during labor will be recorded. These data will be analyzed by their means, with the t-student test, to determine statistical significance.